2010
DOI: 10.1111/j.1742-6723.2010.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress testing before discharge is not required for patients with low and intermediate risk of acute coronary syndrome after emergency department short stay assessment

Abstract: The present study showed that an ED short stay unit can effectively evaluate and manage patients with low and intermediate risk of ACS. The study suggests that patients with low and intermediate risk for ACS might safely be discharged after normal serial ECG and cardiac biomarkers, with a view to early outpatient stress testing. With strict adherence to admission criteria, there does not appear to be any benefit of stress testing before discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The present study did not explore major adverse cardiac events (MACE) over a prolonged follow‐up period. However, analysis among a cohort of patients discharged from the ED at our centre has previously demonstrated a very low proportion of MACE …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The present study did not explore major adverse cardiac events (MACE) over a prolonged follow‐up period. However, analysis among a cohort of patients discharged from the ED at our centre has previously demonstrated a very low proportion of MACE …”
Section: Discussionmentioning
confidence: 90%
“…However, analysis among a cohort of patients discharged from the ED at our centre has previously demonstrated a very low proportion of MACE. 17 Despite providing supportive evidence for the efficacy of single HsTnI, the retrospective nature of this investigation does not capture the clinical outcomes that would have occurred following effective implementation of a single HsTnI threshold of <5 ng/L for discharge decisions. Additional areas for further study would include patient outcome assessment following prospective implementation of single very low HsTnI in ED chest pain pathways, analysis of long-term MACE in these patients and evaluation of the impact on service delivery from earlier discharge of this cohort of patients with very low initial HsTnI results.…”
Section: Discussionmentioning
confidence: 99%
“…8 Rahman et al found that it was safe to discharge patients at low risk for ACS provided they underwent early provocative stress testing 9. NHF/CSANZ guidelines recommend that this should occur within 72 h of discharge 8.…”
Section: Introductionmentioning
confidence: 99%
“…The National Heart Foundation of Australia/Cardiac Society of Australia and New Zealand (NHF/CSANZ) guidelines for ACS management advise patients are risk stratified into high, intermediate or low risk of non‐ST elevation ACS (NSTEACS) (refer to Appendix S1) . Patients who are not high‐risk require further functional or invasive testing, such as exercise stress testing (EST), which should occur before discharge or at early outpatient review . It is recommended this occur within 72 h for intermediate‐risk ACS patients …”
Section: Introductionmentioning
confidence: 99%
“…Further, a prospective clinical audit of an accelerated chest pain assessment protocol performed by Aroney et al . supported the use of inpatient EST in chest pain patients; however, Rahman et al . found that it was safe to discharge patients provided they received early follow‐up EST.…”
Section: Introductionmentioning
confidence: 99%